Analysis of Drug Use and Potential Interactions in Type 2 Diabetes Inpatients at a Type C Hospital, Kediri (2024) - anis akhwan dhafin; Luh Santhi Utami Wiryani; Elsa Mahardika Putri; Herman Herman; Pulung Prabowo; Prayoga Feri Yuniarto; Winartiana Winartiana (LPPM Akafarma Sunan Giri Ponorogo, 2025)
Bachelor of Pharmacy, Universitas Mahasaraswati Denpasar, Indonesia Corresponding Author: anisdhafin13@unik-kediri.ac.id ABSTRACT Type 2 diabetes mellitus (T2DM) is a chronic metabolic disorder with a high prevalence and frequent comorbidities, particularly hypertension, which often require multidrug therapy and increase the risk of drug interactions. This study aimed to analyze the pattern of antidiabetic drug use and the potential for drug interactions in hospitalized patients with T2DM at a type C hospital in Kediri City during June–December 2024. The research employed a retrospective descriptive design using medical record data of 44 patients who met the inclusion criteria. Data were analyzed descriptively and presented in frequency distribution tables. Results showed that the most commonly prescribed drug class was biguanides (26.25%), followed by sulfonylureas (21%), insulin (21%), and α-glucosidase inhibitors (12.5%). Combination therapy was widely used, particularly the combination of two oral antidiabetic agents. Potential drug interactions were identified in 72.73% of patients, with moderate interactions being the most frequent (78.13%), followed by minor (12.5%) and major (9.38%) interactions. The most common interactions included metformin with amlodipine or ramipril (moderate severity), captopril with hydrochlorothiazide (minor severity), and simvastatin with amlodipine (major severity). However, in this study polypharmacy was defined as the concomitant use of ≥5 medications. These findings indicate that such polypharmacy in T2DM patients with hypertension substantially increases the likelihood of drug interactions, underscoring the importance of careful monitoring and rational prescribing to improve patient safety